β-galactosidase Encapsulated in Carrageenan, Pectin and Carrageenan/Pectin: Comparative Study, Stability and Controlled Release - SILVA,RENATA CRISTINA (2020)
Abstract The present study investigated the encapsulation of β-galactosidase in carrageenan, pectin and its hybrid hydrogels by using the ionotropic gelation method. The material obtained was characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TG/DTG) and scanning electron microscopy (SEM). The effects of pH, temperature and storage time were evaluated in terms of the catalytic activity of the free and encapsulated enzyme. Addition studies were conducted evaluating the performance of catalytic activity in vitro conditions. Carrageenan, pectin and hybrid hydrogels presented encapsulation efficiency of 58 ± 1%, 72 ± 1% and 77 ± 2%, respectively. The pectin hydrogel showed the higher β-galactosidase activity in pH and temperature tests. However, the carrageenan hydrogel exhibited best stability after been stored for three months. Carrageenan and pectin hydrogels were 2.0 and 2.4 times more efficiently than commercial tablet in the releasing β-galactosidase under in vitro conditions, respectively. The results suggest that pectin and carrageenan hydrogels may be useful for the development of new formulation of β-galactosidase.